Oral mucosal lesion detection accuracy post lectures and tests in clinical dental students - Amtha, Rahmi; Gunardi, Indrayadi; Cheong, Sok Ching; Zain, R.B. (University of Dicle, 2018)
The oral medicine field of dentistry comprises learning to diagnose oral soft tissue disease and is taught from the third year of dental school. Despite long-term learning on oral medicine, there are no data on the clinical accuracy of oral mucosal lesion (OML) diagnosis by clinical dental students (CDS). Purpose: to evaluate the effectiveness of oral medicine lectures prior to community service in Tanjung Pandan, Indonesia. Methods: An observational study was done by 60 CDS, divided into 3 groups, who were tested and/or given prior lectures. OML detection was performed by CDS and re-confirmed by an oral medicine specialist. The analyses were done by t-test, ANOVA, and Cohen's Kappa. The results: Out of 615 patients, only 243 patients had OML. There was a significant difference in test scores found between groups with or without prior lectures(P=.026; P=.015). The accuracy and inter-agreement of OML detection was good with substantial agreement (AUC=.825; K=.629); however, there was fair agreement on normal variant oral lesions (AUC=.68; k=.322), and all groups failed to detect and diagnose OPMD lesions (AUC=.501; k=.003). There was a positive correlation between test #2 and AUC OML (R=.845), and with every increase in test score, the accuracy is expected to be .033 higher. Dental student OML knowledge should be upgraded by frequent oral lesion case practice. Further educational strategy is needed to develop dental student's knowledge and skill, so that they can integrate their learning into their practice.